KAJIAN EPIDEMIOLOGI KEJADIAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS ROWOSARI KOTA SEMARANG - Asih Prasetyowati (Program Studi Perekam Medis & Informasi Kesehatan, 2019)
Aedes aegypti mosquito is a vector that causes Dengue Hemorrhagic Fever. DHF is one of the top 10 diseases in Indonesia and is also one of the top 10 diseases in the Semarang city. The spread of DHF tends to increase both in the number of events and in the area and sporadically an extraordinary event (KLB) always occurs every year. This study aims to examine epidemiologically DHF events that occur almost every year. This research is a quantitative study, which was conducted in an observational descriptive manner with a retrospective time approach. The incidence of DHF in the Rowosari Community Health Center is mostly found in the male population (56%) and the most age group (65%) is 5-14 years. The sub-district with the highest IR DBD (161.86 / 100000) is the Kramas sub-district. The peak incidence of DHF is April - May in 2019. Based on the DHF epidemiological study, it is recommended that “Eradication Mosquitos Nest” (PSN) continue to carry out its activities in collaboration with Gasurkes. Prevention of mosquito bites is further enhanced by the school age population. PSN activities are not only limited to the indoor environment, but also the external environment such as public places, vacant land and houses. The community service program to clean the surrounding environment needs to be maximized, for example with Clean Friday Activities.